Implementation of Cooperative Character-Based English Learning - Juliansyah, Roni (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Learning English transcends merely mastering grammar and spelling; it encompasses the development of critical thinking, effective communication, and an appreciation for English culture and identity. This study seeks to implement cooperative character education within English courses. Utilizing a library research method with a qualitative approach, the findings indicate that cooperative-based English instruction fosters greater student engagement in the learning process. Students feel more connected and take on active roles in achieving their learning objectives. The incorporation of cooperative character education not only enhances students' essential teamwork skills—such as listening, sharing ideas, and collaborating toward common goals—but also improves their communication abilities in English. Through collaborative learning, students learn to articulate their thoughts, express opinions, and interact with peers in clear, effective, and respectful manners.